MEKANISME PEREKRUTAN KADER PARTAI POLITIK LOKAL (Studi di Banda Aceh) - Benny Erick (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2019)
Indonesia is a democratic country that implements multi party system, approaching political years more and more many new parties were emerging, however a few parties that do not qualified to verification phase. In the party system, Aceh is a privileged region that has specialities because it has local political parties, the existence and establishment of local parties in Aceh has a strong legal base and is regulated in the Aceh Goverment Law of 2006. System and recruitment mechanism in every local party in Aceh are certainlt have a different, this distinction is a spesial strategy developed by the party to capture and absorb framework and sympathizers. This recruitment mechanism is interestingly discussed and review further, in order to see how far the party is able to compete with other parties, and to measure the credibility level of the framework to the party that carried. This study used qualitative research method with the subject of research is the management or official of each Local Political Party in Banda Aceh. Primary data is obtained through direct interview about the mechanism ofrecruiting party cadre while secondary data is obtained from each party's website. The results showed that Local Political Parties in Banda Aceh, namely Nanggroe Aceh Party, Aceh Party, Aceh Regional Party and SIRA Party all used an open recruitment mechanism system because the method was considered effective to recruiting political cadre in terms of quantity and quality because each party had its own criteria in determining cadres who have competencies that are in accordance with the vision and mission of each party. The obstacle faced by all of Local Political Parties in Banda Aceh region is still ineffective in the voting process for women in each party in parliament because the Aceh Province applies Islamic Sharia in its government. The conclusion was that all of Local Political Parties in the Banda Aceh region applied an open recruitment mechanism system because the system was most effective in the process of recruiting party cadres in terms of quantity and quality.